Native life in East Africa - Weule, Karl, 1864-1926; Werner, Alice, 1859-1935 (Salt Lake City, UT : Project Gutenberg, 2023)
"Native Life in East Africa: The Results of an Ethnological Research Expedition" by Dr. Karl Weule is a scientific publication written in the early 20th century. This work chronicles the author's experiences during a research expedition in East Africa, primarily focusing on the various tribes and cultures of the region. Dr. Weule aims to document the customs, languages, and social structures of the native people, striving to provide an insight into their daily lives and the impact of colonialism. The opening of the book introduces Dr. Weule's journey as he embarks on an expedition to study African tribes, beginning in the coastal city of Dar es Salam. As he arrives, he reflects on the beauty and complexity of the region, discussing the historical significance of ports like Mombasa and Zanzibar. Dr. Weule's initial impressions highlight both the challenges and the allure he finds in East Africa, setting the stage for his deeper exploration of its diverse cultures and social dynamics. He establishes that his aim is not only to collect data but to understand the intricate relationships between the natives and the prevailing colonial structures. (This is an automatically generated summary.)
Release date is 2023-08-27
Richard Tonsing, Peter Becker, Jude Eylander, and the Online Distributed Proofreading Team at https://www.pgdp.net (This file was produced from images generously made available by The Internet Archive)
Keywords: Africa, East -- Description and travel; Ethnology -- Tanzania; Ethnology -- Africa, East